Group Cognitive Behavior Therapy (Cbt) Terhadap Penurunan Tingkat Kecemasan Pada Korban Perilaku Kekerasan (Bullying) Di Sekolah Dasar - Siska Damaiyanti; Marizki Putri (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2021)
Background: Based on research data from PISA 2018, it was found that 4 out of 10 students in Indonesia have been victims of bullying. One of the impacts of violent behavior on children (bullying) is anxiety. Objective:The purpose of this study was to address anxiety or the risk of psychosocial disorders by using group cognitive behavior therapy (CBT)in Solok CityMethod: This was quasi experimental study with pre-post test group.The sample in this study were elementary school who had experienced bullying. To measure the level of anxiety in victims of violent behavior (bullying) using a measuring tool or instrument known as the Hamilton Rating Scale For Anxiety (HRS - A)Results and Discussion: the results showed that there was a decrease in anxiety among victims of bullying behavior after Cognitive Behavior Therapy (CBT) group therapy (p = 0.031).Conclusion: CBT can be applied as a method of reducing anxiety that can be given to victims of bullying